Son Jarocho’s Versadoras: cyberorality and Gender Subversion in Evelin Acosta’s Decimario (2021) - Piastro, Julia (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In the last decades, a generation of young female decimistas, writers and improvisers of the poetic form of the décima, has emerged in Mexican tradition of son jarocho. This generation has found in electronic media a tool to make their voice heard and weave community ties in a context of increasing globalization. In this article, I show that the young Mexican poet and musician Evelin Acosta, in her book Decimario (2021), questions the male figure of the troubadour and the tropes of the romantic love associated with it. Her use of print and electronic media takes elements of oral culture and adapts them to contemporary global needs. I conclude that the dissemination of the décima in print and electronic media has become a valuable strategy to preserve and maintain the relevancy of the versada jarocha, as well as a method of interrogating the violence of patriarchal structures in the traditional son.